Integrating Social and Emotional Learning with Content : Using Picture Books for Differentiated Teaching in K-3 Classrooms. - Kapustka, Katherine; Bright, Sarah ([Place of publication not identified] : Routledge, 2022)
Integrating Social and Emotional Learning with Content builds a framework for creatively and effectively using picture books to integrate social and emotional learning (SEL) with teaching across content areas. Thoughtful book choices in mixed-ability early elementary classrooms have the power to not only support gifted students as they develop academically, but also provide an opportunity to address their unique social and emotional needs, such as asynchronous development and an early awareness of complex and challenging issues in their lives and the world at large. Picture books are an invaluable tool for this work because the characters, topics, and settings increasingly represent and celebrate the lived experiences of diverse student populations, supporting culturally responsive teaching. Packed with lesson plans, book lists and more, this book is perfect for teachers in gifted and mixed-ability classrooms as well as homeschooling parents looking to help their children make meaningful connections between their culture, languages, and lived experiences and the academic content and SEL skills they are being taught in the classroom.
1. Introduction 2. Social and Emotional Learning and Gifted Children 3.Choosing Quality Picture Books 4.Matching Children to Books 5.Integrating SEL and Subject Content in Lesson Plans 6.Integrating SEL and STEM Using Picture Books 7. Integrating SEL and Social Studies Using Picture Books 8.Integrating SEL and ELA Using Literary Texts 9. Integrating SEL and ELA Using Informational Texts 10. Conclusion
Keywords: Education, Preschool; Picture books; EDUCATION / Elementary; EDUCATION / Special Education / Gifted